LCL filter based high power density AC/DC converter for fast charging applications - Tuyen, Nguyen Dinh; Tam, Nguyen Van Minh; Hoa, Truong Phuoc (Institute of Advanced Engineering and Science, 2024)
This paper introduces a LCL filter design tailored for a 40 kW three-phase grid-connected converter utilized in electric vehicle onboard fast chargers. In contrast to conventional filters, the LCL filter finds extensive application in AC/DC converters for power factor correction, thanks to its enhanced harmonic reduction and improved stability of the system. The parameters of LCL filter are devised based on considerations such as the system’s power, the frequency of the alternating current (AC) input, and the PWM frequency, determined through simulation and comprehensive theoretical analysis. By implementing a dual-current closed-loop control strategy, the system ensures a robust response for both the current on the AC side of the converter and the voltage on the direct current (DC) side. The analysis of the system’s performance includes rapid dynamic response, system efficiency, AC current harmonic, and DC ripple voltage. Both simulation and experimental results are presented to validate the proposed design for the LCL filter.